Overview on Clinical Relevance of Intra-Tumor Heterogeneity - Stanta, Giorgio; Bonin, Serena (Frontiers in Medicine, 2018)
Today clinical evaluation of tumor heterogeneity today is an emergent issue to improve clinical oncology. In particular, intra-tumor heterogeneity (ITH) is closely related to cancer progression, resistance to therapy, and recurrences. It is interconnected with complex molecular mechanisms including spatial and temporal phenomena, which are often peculiar for every single patient. This review tries to describe all the types of ITH including morpho-histological ITH, and at the molecular level clonal ITH derived from genomic instability and non-clonal ITH derived from micro-environment interaction. It is important to consider the different types of ITH as a whole for any patient to investigate on cancer progression, prognosis and treatment opportunities. From a practical point of view analytical methods that are widely accessible today, or will be in the near future, are evaluated to investigate the complex pattern of ITH in a reproducible way for a clinical application.